Irregular colorings of certain classes of corona product and Sierpiński graphs. (2nd January 2022) - Iyer, Radha R.; Somamsundaram, K.
Abstract: Let G be a simple connected graph. A coloring of G is said to be irregular if the vertices receives distinct color codes. The minimum number of color codes required to color the graph G is called the irregular chromatic number and it is denoted by χir ( G ). In this paper, we obtain the irregular coloring number for certain classes of corona product of graphs and Sierinski graphs.